Sui generis EMU - Eichengreen, Barry J.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
The thesis of this paper is that there is no historical precedent for Europe's monetary union (EMU). While it is possible to point to similar historical experiences, the most obvious of which were in the 19th century, occurred in Europe, and had "union" as part of their names, EMU differs from these earlier monetary unions. The closer one looks the more uncomfortable one becomes with the effort to draw parallels on the basis of historical experience. It is argued that efforts to draw parallels between EMU and monetary unions past are more likely to mislead than to offer useful insights. Where history is useful is not in drawing parallels but in pinpointing differences. It is useful for highlighting what is distinctive about EMU.
Economic Papers